Characterization of Upper Limb Impairments at Body Function, Activity, and Participation in Persons With Multiple Sclerosis by Behavioral and EMG Assessment: A Cross-Sectional Study - Valè, Nicola; Gandolfi, Marialuisa; Mazzoleni, Stefano; Battini, Elena; Dimitrova, Eleonora Kirilova; Gajofatto, Alberto; Ferraro, Francesco; Castelli, Matteo; Camin, Maruo; Filippetti, Mirko; De Paoli, Carola; Picelli, Alessandro; et al. (Frontiers in Neurology, 2020)
Background: Multiple sclerosis (MS) is a chronic inflammatory demyelinating and disabling disease which primarily affects individuals in their early life between 20 and 40 years of age. MS is a complex condition which may lead to a variety of upper limb dysfunctions and functional deficits. Objective: To explore upper limb impairments at body function, activity and participation in persons with Multiple Sclerosis (PwMS) and severe hand dexterity impairment by behavioral and surface Electromyography (sEMG) assessments. Methods: This observational cross-sectional study involved 41 PwMS with severe hand dexterity impairment stratified according to the Expanded Disability Status Scale (EDSS) into mild-moderate (n=17; EDSS:1-5.5), severe ambulant (n=15; EDSS:6-6.5) and severe non-ambulant (n=9; EDSS: 7-9.5). Behavioral outcome measures exploring body function, activity and participation were administered. The sEMG activity of 6 upper limb muscles of the most affected side was measured during a reaching task. Results: The most severe group was significantly older and more affected by secondary progressive MS than the other two groups. Positive significant associations between UL deterioration and impairments at different International Classification of Functioning, Disability and Health domains were noted in the most severe group. The progressive decline in manual dexterity was moderately to strongly associated with the deterioration of the overall UL activity (=0.72; p<0.001) and disuse (amount of use =0.71; p<0.001; quality of movement = 0.77; p<0.001). There was a low correlation between manual dexterity and UL function (=0.33; p=0.03). The muscle activation pattern investigated with the sEMG was characterized by a decrease in modularity and timing delay in the wrist extensor muscles activation in the severe ambulant patients (EDSS 6-6.5). Similar impairments were observed in the proximal muscles (anterior deltoid) in the more advanced stages (EDSS7). Conclusion: Behavioral assessment, together with measures of muscle activation patterns, allows investigating the pathophysiology of UL impairments in PwMS across progressive neurological disability severity to implement task-specific rehabilitation interventions.